(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
In this research work, the leaching behavior of a copper oxide ore sample prepared from the Qaleh-Zari copper mine with a very high grade of 5.4% Cu (malachite and azurite) was investigated to evaluate the effects of significant operating parameters on copper recovery, including sulfuric acid concentration, solid percentage, particle size and agitation speed. Then, response surface methodology (RSM) and central composite design (CCD) were employed to optimize the leaching process and assess interactions between the effective parameters. In order to further analyze the leaching behavior, kinetics of copper dissolution was studied on the basis of the shrinking core models (SCM). The results showed a reduction in the rate of recovery with an increase in the solid percentage and/or particle size. In contrast, any increase in the agitation speed and/or acid concentration was found to improve the recovery. It was remarkable that increasing the sulfuric acid content, beyond a certain level, imposed no significant effect on the recovery. Optimal copper recovery was obtained with a solid percentage, agitation speed, particle size, and sulfuric acid concentration of 25.12%, 586 rpm, 70 µm, and 12.5%, respectively, leading to a recovery of 93.24%. A study on the leaching kinetics indicated that the dissolution rate was controlled by the fluid diffusion from product layer model with 30.71 kJ/mol of activation energy.